Oligodendrocyte, Astrocyte, and Microglia Crosstalk in Myelin Development, Damage, and Repair - Domingues, Helena S.; Portugal, Camila C.; Socodato, Renato; Relvas, João B. (Frontiers in Cell and Developmental Biology, 2016)
Oligodendrocytes are the myelinating glia of the central nervous system. Myelination of axons allows rapid saltatory conduction of nerve impulses and contributes to axonal integrity. Devastating neurological deficits caused by demyelinating diseases, such as multiple sclerosis, illustrate well the importance of the process. In this review, we focus on the positive and negative interactions between oligodendrocytes, astrocytes and microglia during developmental myelination and remyelination. Even though many lines of evidence support a crucial role for glia crosstalk during these processes, the nature of such interactions is often neglected when designing therapeutics for repair of demyelinated lesions. Understanding the cellular and molecular mechanisms underlying glial cell communication and how they influence oligodendrocyte differentiation and myelination is fundamental to uncover novel therapeutic strategies for myelin repair.